Event review: Center for American Archeology Flintknapping Workshop with Tim Dillard, Kampsville, Illinois, U.S.A. - Binning, Jeanne Day (Journal of Lithic Studies, 2014)
Center for American Archeology Flintknapping Workshop with Tim Dillard, Kampsville, Illinois, USA. May 2014.